Influence of different temperature and relative humidity levels on the mycelial growth, conidial germination and anthracnose incidence of Colletotrichum gloeosporioides - R. Udhayakumar (Innovations in Agriculture)
Mango anthracnose caused by Colletotrichum gloeosporioides is a highly destructive pathogen that causes considerable damage, inflicting severe qualitative and quantitative losses. Among the external factors which influence the growth of fungi, temperature and relative humidity plays an important role. Each pathogen has got its own cardinal temperature and relative humidity, also understanding about these factors will help to standardize the management strategies. Among the six temperature levels tested, 25°C was found to be more conducive for the mycelial growth (88.33 mm), conidial germination (69.00%) of C. gloeosporioides, and maximum disease development (97.00 %) which was followed by room temperature (28+2°C).The maximum disease incidence of 97.00 per cent in the fruits was recorded at 25oC followed by room temperature (28±2oC) (83.33 %) after 10 days of inoculation. Among the seven relative humidity levels tested, the maximum mycelial growth (87.00 mm), conidial germination (72.00%) and maximum disease incidence (97.00 %) was recorded at 100 per cent relative humidity, which was followed by 92.9% relative humidity level (83.00 mm; 61.67% mycelial growth and conidia germination, respectively). The least mycelial growth (7.33 mm) and conidial germination (0.0%) was recorded at 36.8% relative humidity level.